1997
DOI: 10.1136/adc.76.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for mucopolysaccharidosis type I: experience of two British centres

Abstract: (Arch Dis Child 1997;76:92-99)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
141
2
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 20 publications
8
141
2
6
Order By: Relevance
“…However, modern treatments including bone marrow transplantation (BMT) and enzyme replacement therapy (ERT) in MPS I can result in a longer and better quality life for many patients. [18][19][20] ERT is currently licensed for use in MPS I (as Laronidase) and is undergoing clinical trials for use in MPS II and VI. ERT improves respiratory function, endurance, joint mobility, growth (in prepubertal patients), and hair and facial appearance in MPS I.…”
Section: Introductionmentioning
confidence: 99%
“…However, modern treatments including bone marrow transplantation (BMT) and enzyme replacement therapy (ERT) in MPS I can result in a longer and better quality life for many patients. [18][19][20] ERT is currently licensed for use in MPS I (as Laronidase) and is undergoing clinical trials for use in MPS II and VI. ERT improves respiratory function, endurance, joint mobility, growth (in prepubertal patients), and hair and facial appearance in MPS I.…”
Section: Introductionmentioning
confidence: 99%
“…Since enzyme replacement therapy (ERT) is not capable of crossing the blood-brain barrier, HSC transplantation is the treatment of choice for Hurler syndrome. Clinical outcomes include reversal of organomegaly, preservation of neurocognitive development, and improved hearing, vision, and cardiopulmonary function in most transplanted patients (Guffon et al 1998;Whitley et al 1993;Shapiro et al 1995;Peters et al 1996;Vellodi et al 1997;Peters et al 1998;Souillet et al 2003;Aldenhoven et al 2008;Malm et al 2008). However, outcomes are highly variable, and manifestations in certain organ systems continue to progress.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have examined long-term growth for other conditions following HSCT, [22][23][24][25][26][27][28] there are few growth data specific to patients with MPS IH. 17,19 Even less is known about endocrine function in patients with MPS IH after HSCT. One study of five children by Vellodi et al 17 found two had primary ovarian failure, one had sexual infantilism and two had normal pubertal development.…”
Section: Introductionmentioning
confidence: 99%
“…17,19 Even less is known about endocrine function in patients with MPS IH after HSCT. One study of five children by Vellodi et al 17 found two had primary ovarian failure, one had sexual infantilism and two had normal pubertal development. We performed a retrospective chart review of all of our patients with MPS IH who received HSCT at the University of Minnesota between 1983 and 2005, primarily to characterize growth patterns, but also to begin to address the question of endocrine function in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation